Phone Booth - Joel Schumacher; Arian, Waring Ash.; Forest Whitaker; Katie Holmes; Kiefer Sutherland; Paula Jai Parker; Radha Mitchell; Colin Farrell (USA Fox 2000 Pictures, 2002)
A slick New York publicist (Farrell) who picks up a ringing receiver in a phone booth is told that if he hangs up, he'll be killed... and the little red light from a laser rifle sight is proof that the caller isn't kidding.
Stuart Shepard finds himself trapped in a phone booth, pinned down by an extortionist's sniper rifle.
Larry Cohen
Language(s): English, Hungarian
Subtitle(s): English, Turkish, Sebro-Croatian